Gradasi Hujjiyyah Riwayat Asbabun Nuzul Sahabat: Kriteria Pembeda Samʿi dan Raʾyu serta Konsekuensinya dalam Pengambilan Hukum Islam - M. Fahrurrozi; M. Zaki Juliansyah; M. Fadhly Ihdinar; Ali Akbar; Fatmah Taufik Hidayat (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
The Companions of the Prophet (Sahabah) are the primary transmitters of asbab al-nuzul (occasions of Qur'anic revelation), whose direct proximity to revelatory events grants their accounts a unique epistemic privilege. However, not every Companion account constitutes a firsthand historical report (samʿi); some reflect the Companion's own interpretive assessment (raʿy) of how a verse applies to a given situation. This distinction carries profound consequences for Usul al-Fiqh: a samʿi-based account attains the status of al-marfuʿ al-hukmi and functions as authoritative bayan tasyriʿi, while a raʿy based account remains a respected but non binding scholarly opinion. This qualitative library study proposes four verifiable criteria for distinguishing between them: explicit narrative formula, biographical confirmation of the narrator, corroboration by parallel reports, and internal coherence with the verse content. Three case studies demonstrate how this distinction directly affects the normative weight of Companion legal opinions. The conclusion is that a careful, graduated reading of Companion asbab al-nuzul accounts neither blanket acceptance nor blanket skepticism is both methodologically sound and practically necessary for responsible Qur'anic interpretation and legal derivation.